Prevention of drug consumption in the early childhood - Rodríguez Vilchez, Edgar (2004)
The author develops a proposal concerning drug consumption prevention in the early childhood by introducing factors such as family, school, friends, risk and protection, he concludes that a quality education centered on an integral education of all the dimensions and potentialities of children, young people and adults offered in a articulated way by the family, school and society, shall constitute the most effective process to strengthen factors avoiding those risk factors.